Two essays on the persistence of corporate governance practices: the case of political connections and CEO duality (2023)
This dissertation is composed of two essays, the first addresses the question of political connectedness in an emerging market context. The Latin American region allows us to conduct a multicountry study that contributes conclusive evidence on the effect of political connections on firms¿ performance. Similarities among the countries in the study, regarding the political system, legal system, cultural issues, and their historical ties, create an opportunity to understand the impact of political connections, the motivations of firms to persist in seeking these types of individuals and additional results clarify on the dynamics of political connections. The second essay addresses the analysis of CEO/COB separation determinants in a worldwide database. As we observed, many firms persist in the duality of COB/CEO, which means that the same individual simultaneously holds both roles in the same firm. Initially, CEO separation/duality was considered a non-optimal practice, due to the codes of good corporate governance practices disregarding its application. Results offer interesting insights into the motivations of the duality decision. The main reasons are related to the country¿s legal system, market development, and government effectiveness indicators. also, financial indicators influence the CEO structure determination. This dissertation contributes to the literature on corporate governance in several ways. i.) The two essays address the study of original research questions at an international level, ii.) the two essays contribute to explaining the motivations behind the persistence of corporate governance practices, the case of political connections, and the CEO/COB duality, iii.) the datasets have the potential to support additional research in the future.